Epidemiology of Different Types of Cancer in District Dera Ghazi Khan, Pakistan - Saira Bano, Muhammad Sheraz, Haiba Kaul, Khuzeema Tanveer, Zeenat Zafar, Sheikh Muhammad Azam, Shumaila Arif, Shoaib Hassan, Mm Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: Cancer incidence are rising but its prevalence in District Dera Ghazi is not available on government or private level. Therefore, it is difficult to deal with cancer about its statistics and specific type prevalence. Our study was aimed to find the prevalence of cancer in various tehsils of Dera Ghazi Khan District, along with its trend from 2015 to 2021. Method:This was a cross-sectional study, conducted on cancer prevalence in three tehsils of Dera Ghazi Khan includes; DG Khan, Taunsa and Tribal area. A self-made questionnaire was used to assess the cancer prevalence in the form of;gender discrimination, prominent cancer types, number of death per year, number of cancer cases in various tehsils and number of live cancer patients and individuals survived. Results:Total 817 cancer patients were included in this study, 415 belong to Tribal area tehsil. Total 350 female cancer patients were reported in this study, 173 were affected by breast cancer and mostly of them belong to urban area. Breast, blood, liver, throat and stomach cancers were most prevalent in district. Highest proportion of cancer affected individuals were aged between 25 to 65 years. Cancer death rate was found to be in increasing order from 2015 (68) to 2020 (116). 2021 was recorded with 109 deaths. 157 cancer patients were under treatment and only 18 patients could have recovered from cancer in last 5 years. Conclusion:Cancer was highly prevalent in DG Khan especially in tribal area. Reason for high cancer prevalence might be presence of radioactive elements in environment, illiteracy and unavailability of cancer treatment and early diagnose center in DG Khan District. Keywords: Liver Cancer; Epidemiology; DG Khan; Breast Cancer; Colorectal Cancer